Design and Characterization of Concave Hollow Double-Layer Nanospheres for Efficient Cd(II) and Pb(II) Adsorption - Jing, Fangfen; Xu, Xin; Lu, Weiwei; Jin, Mingzhu; He, Xinyang; Yu, Rongtai (Langmuir, 2025)
Polymer-based adsorbents have emerged as promising candidates for heavy-metal remediation due to their tailorable porosity and multifunctional surfaces, yet challenges persist in achieving both structural precision and adsorption efficiency. Here, we report a concave hollow double-layer nanosphere (CHDN) synthesized through a facile self-assembly strategy engineered for selective capture of Cd(II) and Pb(II) ions. Comprehensive characterization via transmission electron microscopy (TEM), scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FT-IR), Raman spectroscopy, and thermogravimetric analysis (TGA) confirmed the hierarchical architecture with abundant amino/hydroxyl moieties. The CHDN demonstrated exceptional adsorption capacities of 198.40 mg/g for Cd(II) and 60.34 mg/g for Pb(II), outperforming conventional adsorbents. Isotherm analysis revealed Cd(II) adsorption followed the Sips model (R 2 > 0.99), while Pb(II) adhered to the Langmuir model, suggesting monolayer and heterogeneous binding mechanisms, respectively. Kinetic studies further corroborated chemisorption dominance through pseudo-second-order fitting for Cd(II) and Elovich compatibility for Pb(II). We propose a synergistic mechanism involving ligand complexation and ion exchange, facilitated by the dual functionality of surface groups and structural advantages of the concave architecture. This work provides a blueprint for designing spatially engineered polymers for environmental remediation.